'Fussy eating' and feeding dynamics: School children's perceptions, experiences, and strategies. (1st June 2022) - Wolstenholme, H.; Kelly, C.; Heary, C.
Abstract: 'Fussy eating' behaviours are associated with increased mealtime stress, fewer family meals, and are considered a barrier to improving children's diets. A better understanding of these behaviours is critical to enable families to have more nutritious and enjoyable meals. Children's perspectives have not been adequately reported due to parents being seen as sufficient proxies in the past, and ethical challenges associated with carrying out research with children. 'Fussy eating' research has shifted to a bi-directional relational model, calling for deeper insight into how children experience, and contribute to, feeding dynamics. This study aims to explore 1) how 'fussy eating' behaviours are perceived, experienced and managed by children and 2) how children experience feeding dynamics relating to these behaviours. Qualitative interviews were conducted using visual tools and vignettes. Participants included 16 children aged 7–10 years. Children did not have to be considered 'fussy eaters' to participate and represented a wide range of Food Fussiness scores on the Children's Eating Behaviour Questionnaire reported by parents. Thematic analysis generated three themes: 1) Paradoxical Perceptions: 'Normal', yet 'Bad' Behaviour; 2) Grappling with Internal Experience and External Expectations and 3) Navigating Food Refusal and Managing Dislikes. The conceptualisation of 'fussy eating' as 'bad' behaviour likely contributes to mealtimes stress. Children described tension between their internal experiences with food (sensory and emotional) and external expectations on their eating. Children are acutely aware of their parents' goals, emotions and practices at mealtimes. In light of these parental expectations, children develop their own strategies for navigating food refusal, negotiating with parents and overcoming dislikes. This study highlights the need to listen to children and work with them to develop meaningful, relevant and effective eating interventions.